PERAN KELOMPOK SADAR WISATA DALAM PENGEMBANGAN DESA WISATA KARANG BAJO KECAMATAN BAYAN KABUPATEN LOMBOK UTARA - Jamilatun Rahmi; Fathurrahim Fathurrahim; Sri Susanty (Journal Of Responsible Tourism, 2022)
This study discusses the role of the Sugriwa Tourism Awareness Group in the development of Karang Bajo Tourism Village, Bayan District, North Lombok Regency. Karang Bajo Village has a tourist attraction in the form of culture that is still maintained its authenticity, nature and also the daily activities of typical rural people. This study uses a qualitative approach with a descriptive qualitative research type. The focus of the research is to examine the role of Pokdarwis Sugriwa by using the theory of tourism destination development by Cooper which consists of Attraction, Accessibility, Amenities, and Ancillary Service. Data collection by interview, observation and documentation methods. The results of the research and discussion show the role of Pokdarwis Sugriwa in the development of the Karang Bajo tourist village based on 4 aspects of developing a tourist village, namely acting as actors of attractions, managers of DTW, custodians of accessibility, providing lack of accessibility, as managers and maintainers of facilities such as lodging, public toilets, halls. and the absence of an active role in additional service facilities such as the absence of collaboration with the nearest tourist village. There are efforts that can be made to increase the role of Pokdarwis Sugriwa in the development of the Karang Bajo tourist village, namely establishing good relationships with stakeholders, increasing the quality and quantity of attractions,